2016
DOI: 10.1128/aem.00526-16
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Application of Bacteriophage as a Potential Therapeutic Agent To Control OXA-66-Like Carbapenemase-Producing Acinetobacter baumannii Strains Belonging to Sequence Type 357

Abstract: The increasing prevalence of carbapenem-resistant Acinetobacter baumannii (CRAB) strains in intensive care units has caused major problems in public health worldwide. Our aim was to determine whether this phage could be used as an alternative therapeutic agent against multidrug-resistant bacterial strains, specifically CRAB clinical isolates, using a mouse model. Ten bacteriophages that caused lysis in CRAB strains, including bla OXA-66-like genes, were isolated. YMC13/01/C62 ABA BP (phage B-C62), which showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 49 publications
(54 reference statements)
2
43
1
Order By: Relevance
“…Even though systemic phage dissemination from the airways is probably not very efficient, phages were demonstrated to reach the lungs by inhalation and in most cases they were capable of controlling bacterial infections in the lungs. Inhalation with phages had a life‐saving effect in hemorrhagic pneumonia caused by Pseudomonas aeruginosa in a mink model, Acinetobacter baumannii ‐ or Klebsiella pneumoniae ‐induced pneumonia in mice, and fatal E. coli respiratory infection in chickens . Experimental pneumonia in mice was reduced by phage therapy in a time‐ and dose‐dependent manner .…”
Section: Entering the Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though systemic phage dissemination from the airways is probably not very efficient, phages were demonstrated to reach the lungs by inhalation and in most cases they were capable of controlling bacterial infections in the lungs. Inhalation with phages had a life‐saving effect in hemorrhagic pneumonia caused by Pseudomonas aeruginosa in a mink model, Acinetobacter baumannii ‐ or Klebsiella pneumoniae ‐induced pneumonia in mice, and fatal E. coli respiratory infection in chickens . Experimental pneumonia in mice was reduced by phage therapy in a time‐ and dose‐dependent manner .…”
Section: Entering the Systemmentioning
confidence: 99%
“…Pseudomonas aeruginosa in a mink model, 96,97 Acinetobacter baumannii-or Klebsiella pneumoniae-induced pneumonia in mice, 98,99 and fatal E. coli respiratory infection in chickens. 100 Experimental pneumonia in mice was reduced by phage therapy in a time-and dose-dependent manner.…”
Section: Respiratory Tractmentioning
confidence: 99%
“…MDR isolates of A. baumannii, including CRAB, can be targets for such bacteriophages, so they are being considered as a useful alternative to face drug resistance. No deleterious side effects associated with their use have been reported [147,148]. Phage Bϕ-C62 has shown the strongest lytic activity [147].…”
Section: Bacteriophages Endolysin (Artilysin)mentioning
confidence: 99%
“…Several rodent studies have suggested that strain-specific phages can improve outcomes from intranasally inoculated lung infection, intraperitoneal sepsis, or wound infections (288,(292)(293)(294). Lysin peptides from phages have also been studied as effective treatments for A. baumannii infections in mice (295,296).…”
Section: Bacteriophagesmentioning
confidence: 99%